BS EN 17176-2 AMD1. Plastics piping systems for water supply and for buried and above ground drainage, sewerage and irrigation under pressure. Oriented unplasticized poly(vinyl chloride) (PVC-O). Part 2. Pipes (24th November 2021) - British Standards Institution,
No abstract available